Ethanol Extract of Artocarpus odoratissimus (Tarap) Bark Inhibit Migration of MDA-MB-231 Triple Negative Breast Cancer Cells - Rachmi, Eva; Hasanah, Nurul; Irawiraman, Hadi; Nuratifah, Annisa Puteri; Nahusuly, Fritz (Indonesian Society for Cancer Chemoprevention, 2023)
Breast cancer is the most diagnosed cancer in the world, with triple negative breast cancer (TNBC) being one of its subtypes that exhibits an aggressive clinical course, a tendency for early metastasis, and a poor prognosis. Tarap (Artocarpus odoratissimus Blanco) is an endemic plant of East Kalimantan, which possesses anticancer potential. This study aimed to explore the ability of ethanol extract of Tarap bark (EETB) in reducing cell viability, inducing apoptosis and inhibiting migration of MDA-MB-231 cells. Cell viability was observed by 3-(4.5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. EETB -induced apoptosis was analyzed by double staining allophycocyanin (APC) Annexin V with PI kit through flow cytometry. Cell migration was determined through scratch assay. EETB was found to decrease cell viability with an IC50 value of 1607.302 μg/ml (R=0.369). EETB’s ability to induce total apoptosis did not show significant differences across various concentrations. EETB was able to inhibit cell migration, especially at concentrations of 800 mg/ml, both at 24-h and 48-h observations. This finding demonstrates that EETB has a weak effect on reducing the viability and inducing the apoptosis of MDA-MB-231 cells. EETB induced morphological cells type change in to globular type and significantly inhibits two-dimensional migration of MDA-MB-231 cells.Keywords: Tarap, Artocarpus odoratissimus, triple negative breast cancer.